IMF Survey, Volume 36 Issue 12. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2007)
Global market turmoil; Strauss-Kahn to head IMF; Global warming; Europe: Financial integration; Islamic finance; Emerging market vulnerability; Subprime turmoil: Lessons; Maghreb integration; Oil producers: Fiscal management; News briefs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet